2022
DOI: 10.7717/peerj-cs.1136
|View full text |Cite
|
Sign up to set email alerts
|

Who is in the sample? An analysis of real and surrogate users as participants in user study research in the information technology fields

Abstract: Background Constructing a sample of real users as participants in user studies is considered by most researchers to be vital for the validity, usefulness, and applicability of research findings. However, how often user studies reported in information technology academic literature sample real users or surrogate users is unknown. Therefore, it is uncertain whether or not the use of surrogate users in place of real users is a widespread problem within user study practice. Objective To determine how often user … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…We want to highlight that this approach enabled us to collect more data points over a shorter period of time than with an in-lab elicitation study: we observed 133 participants in two days (it took us two weeks to recruit 13 in-lab participants in Stage 2). Additionally, conducting Stage 1 in situ (rather than in the lab) mitigated some of the problems of using surrogate users [3] who may not be representative of the target population [4].…”
Section: In Situ Observations: Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…We want to highlight that this approach enabled us to collect more data points over a shorter period of time than with an in-lab elicitation study: we observed 133 participants in two days (it took us two weeks to recruit 13 in-lab participants in Stage 2). Additionally, conducting Stage 1 in situ (rather than in the lab) mitigated some of the problems of using surrogate users [3] who may not be representative of the target population [4].…”
Section: In Situ Observations: Proceduresmentioning
confidence: 99%
“…When conducting elicitation studies, the interaction designers prompt the participants with a system function and ask them what interaction command they would use to activate it. However, they face limitations: recruiting participants for in-lab studies may be a long, expensive, and cumbersome process [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…As such, it is the epitome of ecological validity, but (often) at the cost of internal validity. Implementation scientists (and practitioners) directly study populations who an intervention will impact, in situ, rather than selecting surrogate users [378] to represent the target population (e.g., studying healthy volunteers or excluding patients with comorbidities) [331]. Different terms often utilised interchangeably, have emerged to describe the field of implementation research.…”
Section: Implementation Sciencementioning
confidence: 99%